Fear, Reverence and Ambivalence: Divine Snakes in Contemporary South India - Allocco, Amy (Religions of South Asia, 2013)
In contemporary South Indian Hinduism, nagas are ambivalently imaged: they are divine beings with the capacity to bless as well as to curse. In addition to their primary association with fertility, these divinized non-human animals are perceived as particularly receptive to women's concerns (healing and familial prosperity) and are widely worshipped to obtain these blessings. The ritual propitiation of snake deities is overwhelmingly the practice of women in Tamil Nadu today, where naga deities take multiple manifestations, including that of divine snakes who live in anthills and anthropomorphic goddesses who are installed in temples. Yet nagas who are disturbed or harmed may cause a malefic astrological condition called naga dosam (snake blemish). This astrological flaw, which manifests in inauspicious planetary configurations in an individual's horoscope, is faulted for late marriage and infertility as well as an array of additional negative effects. Drawing on many years of ethnographic fieldwork and textual study in Tamil Nadu, this article describes and analyses myths and narratives that reveal the dual character of nagas as divine beings capable of dispensing blessings, as well as blocking marriage and with holding much-desired offspring. The article also analyses the critical dimension of gender in nagas' narratives, where human males often beat or kill their household's reptilian visitor, while females respond with offerings and reverence.